PENGARUH MODEL PEMBELAJARAN NUMBER HEAD TOGETHER BERBANTUAN MEDIA KOMIK “FLAT WAKE ADVANTURE” TERHADAP KEMAMPUAN PEMECAHAN MASALAH - Akadiyaningsih, Dwi; Roestika Rini, Zulmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
In mathematics learning, problem solving is an important activity when learning mathematics. In mathematics learning, the right media according to the learning model can make the learning process more interesting, easier to understand, according to students' needs. This study aims to examine the effect of the Number Head Together learning model (NHT) assisted by the comic media "flat wake adventure" on the problem-solving abilities of 3rd grade elementary school students. This study uses a quantitative method with a quasi-experimental design, the population in this study is Ketapang 01 Elementary School and the sample in this study is class IIIA as the experimental class while class IIIB as the control class. Data collection techniques are in the form of tests and non-tests. The results of the study showed that there was a significant difference between the experimental and control groups. The average post-test score of the experimental group (86.37) was higher than the control group (79.58). Independent Sample T-test analysis showed a significance value of 0.00 <0.05, this indicates that learning using the Numbered Head Together model assisted by the comic media "flat wake adventure" and the Numbered Head Together model without the comic media "flat wake adventure" resulted in differences in the problem-solving abilities of grade III students. Regression test analysis showed a significance level of 0.001 <0.05. indicating that the Numbered Head Together (NHT) learning model assisted by the comic media "flat wake adventure" has an influence on students' problem-solving abilities